Clinical efficacy of herbal extracts in treatment of mild to moderate acne vulgaris: an 8-week, double-blinded, randomized, controlled trial. (3rd April 2021) - Yang, Ji Hoon; Hwang, Eun Ju; Moon, Jungyoon; Yoon, Ji Young; Kim, Ji Won; Choi, Sungjun; Cho, Soo Ick; Suh, Dae Hun
Abstract: Background: Herbal extracts with fewer adverse effects can be an alternative to these drugs because they can target various molecular pathways of acne pathogenesis. Objectives: To evaluate the clinical efficacy of herbal extracts (mangosteen, Lithospermum officinale, Tribulus terrestris L., Houttuynia cordata Thunb) for the treatment of mild to moderate acne vulgaris. Methods: Sixty patients were randomized in a 1:1 ratio to receive blinded treatment with herbal extracts or vehicle for 8 weeks. Inflammatory and non-inflammatory acne lesion counts, Investigator's Global Assessment, patient's satisfaction and safety profiles were assessed. We also performed skin biopsy at baseline and week 8 to confirm immunological changes with immunohistochemistry staining. Results: By the end of the study period, both inflammatory and non-inflammatory acne lesion counts were significantly decreased in herbal extracts group ( p < .05). In immunohistochemistry staining, expressions of IL-1α, IL-8, and keratin 16 were significantly decreased in herbal extracts group compared to vehicle group from baseline to week 8. There was no serious adverse events in both groups. Conclusions: This herbal extracts can be a new therapeutic option for patients with mild to moderate acne vulgaris who are reluctant to use drugs.